Customized toothbrush handle for patients with limited manual dexterity - Shreya Colvenkar; Priyanka Patra; Linju Vijay (Elsevier, 2022)
Elderly people may have difficulty in grasping and holding tooth brush due to limited hand and finger movement. This article describes a technique of increasing the volume of toothbrush handle with acrylic device that is custom molded to the patient's unique hand. The customized handle will make holding the brush easier and more comfortable thereby contributing to the maintenance of oral hygiene.